Eye movements and scanpaths in the perception of real-world scenes - Humphrey, Katherine Anne (2010)
The way we move our eyes when viewing a scene is not random, but is influenced by both bottom-up (low-level), and top-down (cognitive) factors. This Thesis investigates not only what these influences are and how they effect eye movements, but more importantly how they interact with each other to guide visual perception of real-world scenes.